Cardiovascular medicine prices as an indicator of access to medicines and their rational use - C M. Razzakova; L. E. Ziganshina (Столичная издательская компания, 2019)
Aim. To perform a comparative analysis of cardiovascular medicine prices in 2011 and 2015 and to assess their availability and affordability as a basis for rational pharmacotherapy.Material and methods. We conducted a comparative analysis of prices for cardiovascular medicines in 2011 and 201 5 in Kazan using the World Health Organization and Health Action International (WHO/HAI) methodology, to assess medicines' availability and affordability to ensure their rational use. We studied availability and prices of 71 cardiovascular medicines in public and private pharmacies of the city of Kazan and analyzed procurement prices of these medicines in hospitals. Also we performed pharmacoeconomic cost-minimisation analysis for arterial hypertension pharmacotherapy in 2015. For each medicine, we analyzed the prices for the original brand drug and its lowest-priced generic. We compared medicine prices with international reference prices of 201 0 and 201 5, delivered by the Management Sciences for Health, by expressing them as median price ratio. Recording and analysis were performed using the standardized MS Excel WHO/HAI Workbook.Results. The prices of generic medicines, both in the public and private sectors, decreased relative to reference prices in 2015 compared to 2011. In 201 1 one third of the medicines were purchased as original brands and in 201 5 almost all medicines were procured as generics with a fourfold decrease in prices. In 201 5, depending on the choice of the medicine the annual course of monotherapy of hypertension varied from 208 to 281 05 rubles.Conclusion. Over the five years from 2011 to 2015, there was a general trend of price reduction for generic products relative to reference prices for cardiovascular medicines. But in order to provide rational pharmacotherapy, additional price studies and pharmacoeconomic analyzes are needed, taking into account the changing prices on the pharmaceutical market.